Deconstructing the feminist consciousness - Ibrahim, Syazliyati (Universiti Teknologi MARA, Kedah, 2025)
Emma Watson is a famous Hollywood actress mainly acclaimed for her role as Hermione in the Harry Potter movie series. She has been chosen as a Goodwill ambassador for the United Nations since 2014 to act as a campaigner for UN Women’s HeForShe campaign in supporting gender equality (UN Women Goodwill Ambassador Emma Watson, n.d). When one of the students in my class showed a video of Emma Watson delivering a speech on feminism and how generally people perceive the topic negatively, I felt compelled to write about this misguided conception based on my foray into feminist studies for the last twenty years. In the video, she voices her concern about how battling for women’s rights has always been seen as synonymous with man-hating.